Kinetic and in silico analysis of thiazolidin-based inhibitors of α-carbonic anhydrase isoenzymes - Ekinci, Deniz; Fidan, Ismail; Durdagi, Serdar; Kaban, Seniz; Supuran, Claudiu T. (TAYLOR & FRANCIS LTD, 2013)
Carbonic anhydrases (CAs, EC 4.2.1.1) are inhibited by sulfonamides, inorganic anions, phenols, salicylic acid derivatives (acting as drug or prodrugs). A novel class of CA inhibitors (CAIs), interacting with the CA isozymes I and II (cytosolic) in a different manner, is reported here. Kinetic measurements allowed us to identify thiazolidin-based compounds as submicromolar-low micromolar inhibitors of these two CA isozymes. Molecular docking studies of a set of such inhibitors within CA I and II active site allowed us to understand the inhibition mechanism. This new class of inhibitors bind differently compared to other classes of inhibitors known to date: they were found between the phenol-binding site, filling thus the middle of the enzyme cavity.
Keywords: Carbonic anhydrase; thiazolidin; sulfonamide; docking; enzyme inhibition; THERAPEUTIC APPLICATIONS; ISOZYMES I; PURIFICATION; DERIVATIVES; Biochemistry & Molecular Biology; Pharmacology & Pharmacy